Ilmu Pengetahuan Alam (IPA) dan Filsafat dalam Pengembangan Potensi Lokal untuk Pembelajaran Masa Depan - Asrorul Azizi (LAMBDA : Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
Humans are creatures who have the ability to continue to think and naturally always improve their knowledge. Human nature is naturally full of curiosity, so humans are always looking for answers to their curiosity. Science or science is born from curiosity about phenomena that occur in the natural environment, so that to fulfill their curiosity, humans seek answers through knowledge, and through knowledge will lead to satisfaction so that science/science is increasingly developing and giving birth to new branches of science again. The knowledge obtained comes from the potential around so that it should be considered in science learning so that the concept remains in accordance with the needs of students. Science / science does not speak of knowledge alone, but emphasizes knowledge and truth. Learning with the right concept of science is an effort made so that humans gain a complete understanding. This study aims to determine the role of educational philosophy in the development of science based on local wisdom. The natural wealth around gives birth to local wisdom that is unique and is a potential in the development of science. Science / science in which the study of the natural surroundings uses scientific steps, scientific thinking, and uses scientific frameworks. Philosophy is used to answer science/science problems for humans. This study examines the importance of a person to develop science/science based on local potential as a means of developing science/science learning to instill other concepts such as to students so that they can be more aware of maintaining local wisdom around them.